Female Political Representation and Substantive Effects on Policies: A Literature Review - Zohal Hessami; Mariana Lopes da Fonseca (Institute of Labor Economics (IZA), 2020)
The share of women in political offices has increased considerably over the past few decades in almost every country in the world. Does this matter for policy outcomes? This is the first paper to provide a literature review on the substantive effects of female representation on policies. In developing countries, the increase in female political representation has caused a better provision of public goods, especially with regard to education and health. In developed countries, higher female representation has not affected public policies as measured by spending patterns. However, more recent evidence shows that female representation has induced changes in parliamentary deliberations and specific policy choices (e.g. more public child care) that may not be reflected in the observable composition of public spending. Finally, higher female representation has improved institutional quality by reducing corruption and rent-extraction by those in power.
Keywords: D78; H00; J16; J18; 330; female politicians; gender; political selection; policy preferences; policy choices